Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2005
DOI: 10.3748/wjg.v11.i5.623
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of mitogen-activated protein kinase and its upstream regulating signal in human gastric cancer

Abstract: MAPKs, particularly ERK subclass are overexpressed in the majority of gastric cancers. Overexpression of ERKs is correlated to TNM staging, serosa invasion, and lymph node involvement. The overexpression of p38 most likely plays a prominent role in certain morphological subtypes of gastric cancers. MEK-1 is also overexpressed in gastric cancer, particularly in metastatic lymph nodes. Upregulation of MAPK signal transduction pathways may play an important role in tumorigenesis and metastatic potential of gastri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
46
0
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 75 publications
(50 citation statements)
references
References 26 publications
3
46
0
1
Order By: Relevance
“…Activation of both JNK and p38 has been reported in breast carcinoma, 12 metastatic serous ovarian carcinoma 13 and in gastric cancer 14 whereas activation of JNK and p38 alone has been reported in poorly differentiated liver tumors 15 and in prostate cancer, 16 respectively. A correlation between activated JNK and early stages of nonsmall-cell lung cancers has been described.…”
mentioning
confidence: 99%
“…Activation of both JNK and p38 has been reported in breast carcinoma, 12 metastatic serous ovarian carcinoma 13 and in gastric cancer 14 whereas activation of JNK and p38 alone has been reported in poorly differentiated liver tumors 15 and in prostate cancer, 16 respectively. A correlation between activated JNK and early stages of nonsmall-cell lung cancers has been described.…”
mentioning
confidence: 99%
“…Mitogen-activated protein/ERK kinase 1 (MEK1), when engineered to be constitutively active, can transform mammalian cells to a cancerous phenotype (Cowley et al 1994, Mansour et al 1994, Webb et al 1998, whereas inhibition of MAPK activity can inhibit the growth of Ras-transformed cells in vitro (Dudley et al 1995, Sebolt-Leopold et al 1999. In addition, the activated MAPK or increased levels of MAPK expression have been detected in a variety of human tumors (Oka et al 1995, Sivaraman et al 1997, Hoshino et al 1999, Kim et al 1999, Ahmed et al 2002, Satyamoorthy et al 2003, Liang et al 2005, Takata et al 2005. Thus, the MAPK signaling pathway is a potential target in cancer therapy (Duesbery et al 1999, Tecle et al 1999, Fang & Richardson 2005, Staehler et al 2005.…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the ERK signaling pathway is typically associated with cell survival, proliferation and differentiation and protecting cells against apoptosis, whereas the JNK and p38 cascades are usually involved in promoting cell growth and apoptosis (4). It has been shown that abnormal MAPK expression is correlated with tumorigenesis and metastatic potential for gastric cancer (5). Thus, identifying new tumor suppressor genes or oncogenes that participate in the MAPK pathway could lead to the discovery of new therapies for gastric cancer.…”
Section: Introductionmentioning
confidence: 99%